Review of Europe’s promise: why the European way is the best hope in an insecure age - Zielonka, J (Wiley Blackwell, 2010)
Review of Europe’s promise: why the European way is the best hope in an insecure age. By Steven Hill. Berkeley, CA: University of California Press. 2010. 472pp. Index. Pb.: £16.95. isbn 978 0 52026 137 2 and Europe as the would-be world power: the EU at fifty. By Giandomenico Majone. Cambridge: Cambridge University Press. 2009. 259pp. Index. Pb.: £19.99. isbn 978 0 52175 845 1.